THE RESULTS OF A SOCIOLOGICAL SURVEY: THE IMPACT OF DIGITALIZATION ON STUDENTS AT UNIVERSITIES - Turganbayeva, А.Р.; Shakhan, А.Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article presents the results of studies to identify the risks that arise in the process of digitalization. At the beginning of the article, the characteristics of the risks of digitalization of education were given, and the attitude of students to the digitalization of education using a survey was determined as social methods for identifying risks and analyzing them. The survey was conducted among students of the East Kazakhstan, West Kazakhstan regions and the city of Almaty. The results of the survey revealed the advantages and disadvantages of the digitalization process in education, pedagogical risks, psychological risks, cognition risks and, in general, the importance of digitalization in modern education. Future educational technologies and learning platforms must take into account the prevention of these risks. According to the respondents' answers, the decrease in direct communication and the need to combine the training format with distance e-learning and classroom training are determined.